Effects of donor/recipient human leukocyte antigen mismatch on human cytomegalovirus replication following liver transplantation. Issue 1 (9th January 2015) - Aldridge, R.W.; Mattes, F.M.; Rolando, N.; Rolles, K.; Smith, C.; Shirling, G.; Atkinson, C.; Burroughs, A.K.; Milne, R.S.B.; Emery, V.C.; Griffiths, P.D.
Abstract Background Natural immunity against cytomegalovirus (CMV) can control virus replication after solid organ transplantation; however, it is not known which components of the adaptive immune system mediate this protection. We investigated whether this protection requires human leukocyte antigen (HLA) matching between donor and recipient by exploiting the fact that, unlike transplantation of other solid organs, liver transplantation does not require HLA matching, but some donor and recipient pairs may nevertheless be matched by chance. Methods To further investigate this immune control, we determined whether chance HLA matching between donor (D) and recipient (R) in liver transplants affected a range of viral replication parameters. Results In total, 274 liver transplant recipients were stratified according to matches at the HLA A, HLA B, and HLA DR loci. The incidence of CMV viremia, kinetics of replication, and peak viral load were similar between the HLA matched and mismatched patients in the D+/R+ and D−/R+ transplant groups. D+/R− transplants with 1 or 2 mismatches at the HLA DR locus had a higher incidence of CMV viremia >3000 genomes/mL blood compared to patients matched at this locus (78% vs. 17%; P = 0.01). Evidence was seen that matching at the HLA A locus had a small effect on peak viral loads in D+/R− patients, with median peak loads of 3540 and 14, 706 genomes/mL in the 0 and combined (1 and 2) mismatch groups, respectively (P = 0.03). Conclusion Overall, our data indicate that, in the setting of liver transplantation, prevention of CMV infection and control of CMV replication by adaptive immunity is minimally influenced by HLA matching of the donor and recipient. Our data raise questions about immune control of CMV in the liver and also about the cells in which the virus is amplified to give rise to CMV viremia.